2023
DOI: 10.1097/nmd.0000000000001705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Moral Injury, Burnout, Anxiety, and Depression in Healthcare Workers 2 Years in to the COVID-19 Pandemic

Robert P. Lennon,
Jessica Parascando,
Simon G. Talbot
et al.

Abstract: COVID-19 has led to marked increases in healthcare worker distress. Studies of these phenomena are often limited to a particular element of distress or a specific subset of healthcare workers. We administered the Moral Injury Symptom Scale for Healthcare Professionals, Copenhagen Burnout Inventory, Patient Health Questionnaire-9, and Generalized Anxiety Disorder-7 via online survey to 17,000 employees of a large academic medical center between December 2021 and February 2022. A total of 1945 participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…No studies were identified through reference list review or EThOS. However, we identified one eligible thesis (de Groot, 2021 ), one accepted manuscript in press (Lennon et al, 2023 ), two pre-prints in Google Scholar (Ma et al, 2022 ; Thomas et al, 2023 ), and one eligible thesis in ProQuest Dissertations (Kimble, 2023 ). Additionally, when contacting authors from one eligible article (Morris et al, 2022 ), they shared data from a recently finalised, unpublished study (Morris, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies were identified through reference list review or EThOS. However, we identified one eligible thesis (de Groot, 2021 ), one accepted manuscript in press (Lennon et al, 2023 ), two pre-prints in Google Scholar (Ma et al, 2022 ; Thomas et al, 2023 ), and one eligible thesis in ProQuest Dissertations (Kimble, 2023 ). Additionally, when contacting authors from one eligible article (Morris et al, 2022 ), they shared data from a recently finalised, unpublished study (Morris, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…As our findings raise concerns about HCWs’ mental health in the COVID-19 era, it is essential to underscore that these concerns apply to active HCWs regardless of setting. As society may have moved on from the COVID-19 pandemic, its impact on the mental health of HCWs may persist (Lennon et al, 2023 ). Further studies should investigate in the long term if the relationship between MI and mental health problems increases in different areas of practice.…”
Section: Discussionmentioning
confidence: 99%